Dutch Public health Foresight Study, in the light of COVID-19. (20th October 2021) - Hilderink, H; Eisinger, E
Abstract: Background: The future consequences of the corona pandemic for health are significant but uncertain. The Dutch Public health Foresight Study-2020 (PHFS-2020) analyses future trends in health status, determinants, prevention and care, in the light of COVID-19. The pandemic impacts health directly through COVID-19 and indirectly through changes in lifestyle, reduced regular care and socio-economic developments. Methods: The Dutch PHFS-2020 applies a scenario approach which explores short- and long-term trends and their possible effect on health and health care. A Trendscenario is used, in combination with three scenarios for the future course of the pandemic and socio-economic developments. Based on these scenarios, societal challenges for the future are identified. Results: In 2020, COVID-19 was the most important causes of death in 2020, life expectancy was almost a year lower and the disease burden of the first wave was almost five times higher than an average flu season. The increase in overweight and smoking will lead to more health loss in the future, including increased mortality. The negative impacts of reduced health care and mental health are already visible and might worsen in the future. The socio-economic and intergenerational divides might become more prominent. Conclusions: The PHFS-2020 shows that indirect effects of the crisis might be taken into account when considering future policy interventions targeting COVID-19. Negative impacts on mental health, possible increase of health inequalities and the long term effects of changes in life style are important indirect effects to be considered by policy makers. Next, a further ageing population might increase the vulnerability for possible future outbreaks. Key messages: The results of this study supports broader consideration of measures and to be better prepared in the future. Public Health foresight help to be better prepared for future possible developments.